Analisa Senyawa CO hasil pembakaran Sepeda Motor Dengan Menggunakan Bahan Bakar Premium Dan Pertamax - Lelawati lelawati (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2019)
Abstract Air pollution is a major threat to humans, which results from motor vehicle fumes. Each combustion process will produce dangerous exhaust gas products that have a negative impact on human health and the environment, if the composition is above the threshold. One of the exhaust gas content is CO gas (Carbon Mono Oxide). Two methods can be used to reduce motor vehicle emissions, namely: First, by increasing knowledge about the selection of fuel (HC), the second provides further treatment of vehicles by periodic maintenance of the motor vehicle.